2006
DOI: 10.1177/0256090920060203
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Retail Service Quality: An Empirical Assessment of the Instrument

Abstract: Retailing in India is growing at the rate of about 18-20 per cent per annum. As part of its strategy to gradually open it up to foreign competition, the government is also in the process of increasing foreign direct investment in the retail sector. At the same time, the urban consumer is becoming more discerning and demanding as far as the lifestyle is concerned. Urban Indian household income and purchasing power are also on the rise. Under such circumstances, the success of organized retailing in India mainly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(34 citation statements)
references
References 25 publications
0
32
1
1
Order By: Relevance
“…The retailers are highly expected to provide avenues that would give maximum value for the money and time spent by the customers. The retail arena today is very different-the opportunities are incredible but exploiting them is extremely tough (Parikh, 2006). Retailers need to continuously focus on areas under their control; this may give them an edge over their competitors and to survive in the economic crisis.…”
Section: Evaluation Of Retail Service Quality-a Fuzzy Ahp Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The retailers are highly expected to provide avenues that would give maximum value for the money and time spent by the customers. The retail arena today is very different-the opportunities are incredible but exploiting them is extremely tough (Parikh, 2006). Retailers need to continuously focus on areas under their control; this may give them an edge over their competitors and to survive in the economic crisis.…”
Section: Evaluation Of Retail Service Quality-a Fuzzy Ahp Approachmentioning
confidence: 99%
“…She concluded that the RSQS dimensions were not valid in India. Parikh (2006) studied the applicability of RSQS in Indian retail and found that the five dimensions are still useful and the overall reliability of the instrument is quite acceptable. He also suggested that once the factors are appropriately modified, the instrument can very well be utilized under the Indian conditions as well.…”
Section: Service Quality Attributes In Retailmentioning
confidence: 99%
“…Collectivism does not play a role as a moderator on the relationship quality -behavioural intentions and service quality behavioural intentions in a low social interaction culture. Parikh (2006) used the RSQS to examine its applicability in Indian retail sector. The results suggest that the scale was reliable for measuring retail service quality.…”
Section: Retail Service Qualitymentioning
confidence: 99%
“…We have already started to see scholarly interest in that direction (Asakawa & Som, 2008;Khanna, 2009) but greater focus is required. Few important sectors such as automobiles, tourism, retail, healthcare, and IT-enabled services/BPO have not been extensively researched although these are growing in the Indian context Lahiri, Kedia, Raghunath, & Agrawal, 2009;Parikh, 2006;Sarkar, 2009). Future research may address the progress that has been made in these sectors.…”
Section: Future Research Agendamentioning
confidence: 99%